Bentuk-Bentuk Kearifan Lokal Dalam Kehidupan Masyarakat Indonesia Sebagai Sumber Gagasan Berkarya Seni Rupa - Syamsiar, Syamsiar (Institut Seni Indoensia Surakarta, 2010)
Indonesia is an archipelagic nation which has approximately 1128 race, with plenty of cultural diversity and varied, each region contributing to the local distinctiveness of the culture in the form of customs, language, architecture, music, dance, decoration, fashion district, traditional food, and others. History shows us about how the local arts of the past are able to adapt the art that comes from outside and is able to transform the local culture in Indonesia, and has produced many stunning works of art in the form of prehistoric art, classical and traditional arts other. The values of life that grows in society tribes in the area of Indonesia, which relies on the wisdom of the natural environ-ment is a source of cultural wealth of a nation that needs to be maintained and preserved. Indonesia is a cha-llenge for artists today to be able to create works of art that has the characteristics or character in his work, with roads dug indigenous people of Indonesia to be imple-mented in his artwork.Keywords:Â Local Wisdom, and Artwork